2006
DOI: 10.1002/dmrr.656
|View full text |Cite
|
Sign up to set email alerts
|

Low‐intensity exercise increases skeletal muscle protein expression of PPARδ and UCP3 in type 2 diabetic patients

Abstract: Background Physical exercise provides health benefits for people with type 2 diabetes mellitus, partly by enhancing skeletal muscle insulin action. We tested the hypothesis that changes in expression of key genes in skeletal muscles relate to exercise-induced improvements in type 2 diabetic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
93
1
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 106 publications
(105 citation statements)
references
References 37 publications
7
93
1
4
Order By: Relevance
“…These results are in agreement with another study showing that changes in plasma glucose concentration and HbA 1c , induced by increased physical activity and weight-loss, were significantly associated with increased mitochondrial content [27]. Interestingly, it has been suggested that insulin-resistant participants may have a lower response to physical training [28]. Recently it was shown that the response to acute exercise in terms of expression and protein content of genes coding for mitochondrial biogenesis was lower in insulin-resistant non-diabetic participants than in lean control participants [29].…”
Section: Introductionsupporting
confidence: 92%
“…These results are in agreement with another study showing that changes in plasma glucose concentration and HbA 1c , induced by increased physical activity and weight-loss, were significantly associated with increased mitochondrial content [27]. Interestingly, it has been suggested that insulin-resistant participants may have a lower response to physical training [28]. Recently it was shown that the response to acute exercise in terms of expression and protein content of genes coding for mitochondrial biogenesis was lower in insulin-resistant non-diabetic participants than in lean control participants [29].…”
Section: Introductionsupporting
confidence: 92%
“…ES for each of the controlled trials was interpreted according to the method of Cohen [16]. from 18 studies including 3 randomized controlled trials reported in 9 publications [17][18][19][20][21][22][23][24][25] (2 trials reported in 8 publications with resistance training [17][18][19][20][21][22][23][24] and 1 with aerobic training [25]), 2 non-randomized controlled trials [26,27] (with aerobic training [26,27]) and 13 uncontrolled trials reported in 15 publications [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] (11 trials reported in 13 publications with aerobic training [28,[30][31][32][33][34][35][36][37][38]…”
Section: Discussionmentioning
confidence: 99%
“…The study quality was performed for three randomized controlled trials reported in nine publications [17][18][19][20][21][22][23][24][25] and two nonrandomized controlled trials [26,27]. In general, the study quality was moderate, and none of the studies met all of the Delphi list quality criteria.…”
Section: Study Quality Assessmentmentioning
confidence: 99%
See 2 more Smart Citations